KESANTUNAN BERBAHASA PADA POSTINGAN LAYANAN AKUN CUSTOMER CARE DALAM TWITTER (SEBUAH KAJIAN PRAGMATIK) - Angel Rigal Permata Setiawan, - (2020)
This research with the title of Speech Acts Politeness in Customer Care's Service Post on Twitter Account (a Pragmatic Study) aims to identify and describe the use of the politeness principle, the application of the politeness principle, and the language politeness scale which refers to the theory of Geoffrey Leech, which is in the post of customer complaints to customer care accounts and responses from customer care accounts. The research approach used in this research is a qualitative approach with the observation method. Data were collected by using proficiency-free techniques and note-taking techniques. The data taken is in the form of a screenshot containing service posts on Twitter which are then transcribed and analyzed. The results of this study indicate that the six maxims of language politeness according to Geoffrey Leech's theory are used in every speech in customer care account service posts on Twitter. The data that has been analyzed shows that there are more speeches that obey the politeness principle than those that violate the politeness principle. The results of this study also indicate that the three language politeness scales according to Geoffrey Leech are used well in the speech data of this study.